2018
DOI: 10.1021/acsabm.8b00020
|View full text |Cite|
|
Sign up to set email alerts
|

New Near-Infrared Fluorescent Probes with Single-Photon Anti-Stokes-Shift Fluorescence for Sensitive Determination of pH Variances in Lysosomes with a Double-Checked Capability

Abstract: Two near-infrared luminescent probes with Stokes-shift and single-photon anti-Stokes-shift fluorescence properties for sensitive determination of pH variance in lysosomes have been synthesized. A morpholine residue in probe A which serves as a targeting group for lysosomes in viable cells was attached to the fluorophores via a spirolactam moiety while a mannose residue was ligated to probe B resulting in increased biocompatibility and solubility in water. Probes A and B contain closed spirolactam moieties, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…In order to test this hypothesis, we conducted colocalization experiments by using commercial Lysosensor Green to determine the intracellular location of probe A . Intracelluar pH values were adjusted by incubating HeLa cells in different pH buffers containing 10 µM nigericine, H + ionphore, which is employed to promote equilibration between intracellular and extracellular pH values [ 7 , 9 , 29 , 41 , 42 ]. Probe A responds sensitively to intracellular pH decreases from 7.01 to 3.50 with gradual fluorescence enhancement due to acid-activated spirolactam ring opening with significantly enhanced π-conjugation, Figure 12 .…”
Section: Resultsmentioning
confidence: 99%
“…In order to test this hypothesis, we conducted colocalization experiments by using commercial Lysosensor Green to determine the intracellular location of probe A . Intracelluar pH values were adjusted by incubating HeLa cells in different pH buffers containing 10 µM nigericine, H + ionphore, which is employed to promote equilibration between intracellular and extracellular pH values [ 7 , 9 , 29 , 41 , 42 ]. Probe A responds sensitively to intracellular pH decreases from 7.01 to 3.50 with gradual fluorescence enhancement due to acid-activated spirolactam ring opening with significantly enhanced π-conjugation, Figure 12 .…”
Section: Resultsmentioning
confidence: 99%
“…Utilizing the metachromatic nature of toluidine blue, the stained tissue was fluoresced using a 488 nm laser [36] in order to image the mast cells which contained an altered Stokes shift in the metachromatically shifted dye. [37] This allowed imaging of the mast cells which were fluorescent under 488 nm illumination and the emission was captured at 647nm. [38] Images were obtained using an Olympus laser scanning confocal microscope and associated Fluoview software (Olympus America, Melville, NY) and analyzed using ImageJ.…”
Section: Toluidine Blue Stainingmentioning
confidence: 99%
“…HBA assisted ASPL has attracted growing interest in recent years due to potential application in various fields, such as photovoltaic energy conversion [50], photoluminescence bioimaging [51], thermal probes [52], optical refrigeration of solids [53][54][55][56], etc. It was shown that this type of up-conversion can take place both in inorganic materials, such as rare-earthdoped crystals [57][58][59], II-VI [60,61], InP [62], PbS [63] semiconductor quantum dots, InP and GaAs bulk semiconductors [64], inorganic perovskite nanoparticles [65][66][67], carbon nanotubes [68], and some organic dyes based on rhodamine [69], porphyrin [70], spirolactam moieties under acidic conditions [71], polymethine [72], fluorescein and oxazine [49].…”
Section: Thermal-assisted Up-conversionmentioning
confidence: 99%